Desempenho e divergência genética de genótipos de tomate para processamento industrial - Bittar, Cecília Alves (2011)
The growth of processing tomato market makes national and multinational seed companies interested to develop new hybrids for this segment. Thus, it becomes necessary to analyze, in Brazilian field conditions, the main agronomic characters and performance of new hybrids. This study evaluated the performance and genetic divergence of tomato genotypes for fruit firmness, fruit set concentration, index of peduncle retention, plant vigor, fruit coverage by leaves, plant health, average yield per plant and soluble solids content (°Brix). Fifty three hybrids were evaluated, with three controls, including H9553, the most planted in Brazil. Only 12 genotypes and the commercial hybrid H9553 met the required criteria for processing tomatoes, based on the characteristics: fruit firmness, fruit set concentration and absence of peduncle retention index (jointless). Genotypes 1, 18 and 48 stood out for soluble solids contents, fruit set concentration and firmness, respectively. The genetic divergence analysis and grouping revealed that genotypes 1 and 18 present dissimilarity from the other genotypes. While the first one had greater averages of plant vigor, fruit leaf cover, plant health and ° Brix, the second one had the lowest averages for fruit firmness, fruit set concentration and ° Brix. Hybrids 3, 6, 8, 14, 24, 37 and 48 showed genetic similarity with the commercial hybrid H9553, which characterizes them as potential for generating new hybrids with high yield and quality, which reflects on the acceptability by industrial tomato production chain.